Advanced Imaging Modalities for the Assessment of Osteoarthritis: A Systematic Review - Danny Marga Rezha; Aria Chandra Gunawan Triwibowo Soedomo (The International Journal of Medical Science and Health Research, 2025)
Introduction: Osteoarthritis (OA) is a whole-joint disease, yet its assessment has traditionally relied on radiography, which has known limitations in visualizing soft tissue and early cartilage changes. This systematic review evaluates the utility and performance of various imaging modalities in the comprehensive assessment of OA. Methods: A systematic review of the literature was conducted to identify studies comparing imaging techniques (radiography, MRI, CT, ultrasound) for OA assessment. Key studies were evaluated for design, population, and outcomes. A risk of bias assessment was performed for pivotal longitudinal and comparative studies. Data on diagnostic performance, correlation with clinical symptoms, and prediction of disease progression were synthesized. Results: The analysis included studies evaluating radiography, MRI, CT, and ultrasound. MRI was consistently found to be the most sensitive modality for whole-organ assessment, capable of detecting cartilage defects, bone marrow lesions (BMLs), and synovitis before they are radiographically apparent. Radiographic joint space narrowing (JSN) proved to be a specific (91%) but insensitive (23%) marker for MRI-detected cartilage loss.1 BMLs and synovitis on MRI were significantly associated with clinical outcomes; BMLs strongly predicted knee pain and future joint replacement (OR 1.57).2 Ultrasound demonstrated superiority over radiography in detecting osteophytes and soft-tissue inflammation.5 A high prevalence of MRI abnormalities was found in radiographically normal and asymptomatic knees, highlighting a significant clinic-radiological discordance.8 Discussion: The findings confirm a paradigm shift from a cartilage-centric view to a whole-organ understanding of OA, driven by advanced imaging. While radiography remains the first-line tool in clinical practice due to accessibility, its limitations for monitoring progression and detecting early disease are profound. MRI, particularly with quantitative techniques, is the gold standard for research and complex cases, identifying key prognostic markers like BMLs. The high prevalence of imaging findings in asymptomatic individuals complicates their use for routine diagnosis but underscores their potential for identifying disease phenotypes and therapeutic targets. Conclusion: Advanced imaging modalities, particularly MRI, provide a comprehensive assessment of OA pathology that far exceeds the capabilities of conventional radiography. The future of OA management will likely involve an imaging-guided approach to phenotype patients and tailor interventions, moving toward a more personalized treatment strategy.